Contextual Effect of “Posyandu” in the Incidence of Anemia in Children under Five - Rokhayati, Rokhayati; Salimo, Harsono; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: Iron deficiency can cause anemia which adversely affects children's growth, especially in terms of achievement, quality of life, and performance as human resources in the future. Birth weight, exclusive breastfeeding complementary feeding (EBF-CF) have a direct relationship with the incidence of anemia in infants. The purpose of this study is to examine the factors that influence anemia in children under five at the Banguntapan II Bantul Health Center, Yogyakarta.Subjects and Method: The cross sectional study was conducted at 25 posyandu in the working area of Banguntapan II Bantul Health Center, Yogyakarta, Indonesia. A sample of 200 children aged 24–60 months was selected by simple random sampling. The dependent variable is anemia in infants. Independent variables are exclusive breastfeeding, breastfeeding, birth weight, nutritional status (BB / TB), mother's education, and mother's work. Anemia data was measured by Hb meter, other variable data were collected using questionnaires. The data were analyzed using a multiple logistic regression with a multilevel approach.Results: The risk of anemia in infants is reduced by exclusive breastfeeding (b = –5.77; 95% CI = -11.30 to -0.24; p = 0.041), EBF-CF administration is appropriate (b = –12.24; 95% CI = -22.47 to -2.00 , p = 0.019), birth weight 2500–4000 g (b = –5.04; CI 95% = -9.87 to 0.21; p = 0.040), good nutritional status (-2SD - + 2SD) (b = –9.11; CI 95% = -17.99 to 0.23; p = 0.044), high maternal education (high school) (b = -10.96; 95% CI = -20.61 to 1.31; p = 0.026), and mothers who work at home (b = -5.98; 95% CI = -11.27 to -0.68; p = 0.026). Posyandu strata showed that there was a contextual influence of posyandu on variations in anemia incidence (ICC = 62.62%).Conclusions: Exclusive breastfeeding, proper EBF-CF, normal birth weight, good nutritional status, high maternal education, and mothers working at home reduce the risk of anemia in infants.Keywords: anemia, children under five, exclusive breastfeeding, multilevelCorrespondence: Rokhayati. Public Health Master’s Program, Universitas Sebelas Maret, Surakarta, Jl. Ir. Sutami No. 36 A, 57126, Surakarta, Jawa Tengah.Email: ocharochayati1991@gmail.com. Mobile +6285328014414Journal of Maternal and Child Health (2019), 4(6): 1-10https://doi.org/10.26911/thejmch.2019.04.06.01